Caribbean hydroclimate and vegetation history across the last glacial period - Warken, Sophie F.; Spötl, Christoph; Bahr, André; Mangini, Augusto (Quaternary science reviews, 2019)
We present a new speleothem trace element and stable isotope record, which extends previous paleoclimate evidence from Cuban speleothems to the last 96 ka. Multiple proxies were used to reconstruct Caribbean hydroclimate and vegetation variability on orbital to millennial timescales. In particular, our proxies indicate a shift to more abundant C4 (compared to C3) vegetation and/or reduced soil activity during the Last Glacial Maximum. Our results confirm the close link of Caribbean precipitation to North Atlantic climate variability, insolation and the strength of the AMOC. The associated variations in Caribbean SSTs and the shift of the ITCZ led to substantial changes of the hydrological cycle. During Heinrich stadials and the Younger Dryas, climatic conditions in Cuba were comparably cool and/or dry. In contrast, warm Dansgaard/Oeschger cycles were accompanied by wetter conditions. This is in agreement with previous evidence for the Holocene, when North Atlantic cold (warm) events coincided with drier (wetter) conditions in Cuba. However, our record suggests that this connection was less dominant during MIS 4 to 2, displayed by a weaker response of Cuban precipitation proxies to North Atlantic climatic shifts than during MIS 5 in particular. We hypothesize that this weaker connection was mediated by the southerly shifted ITCZ inducing a weakening of the northern branch of the Caribbean Low Level Jet which usually transports moisture into the northern Caribbean. This is strikingly evident during the deglacial, when driest and/or coolest conditions prevailed in western Cuba from HS 1 into the Younger Dryas, including the Bølling/Allerød interstadial.
Gesehen am 30.09.2019